(untitled) (Szociológiai Szemle, 2024)
The present paper is a first attempt to write the chronicle of the Research Group of Sociology of the Hungarian Academy of Sciences between 1960 and 1968. This „workshop” was the framework of the exciting work of starting anew, full of contradictions, achievements and failures. However, to the understanding of its establishment the institutional antecedents should be discussed: those conditions which prepared and forced the reorganisation of Hungarian sociology, the setting up of a sociological division within the Institute of Philosophy in the spring of 1960, which had been in operation for three years and from which an autonomous research group, breaking through the narrow bonds, entered the scene of Hungarian social sciences.